2011
DOI: 10.1021/ja2018477
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Labeling Using Engineered Variants of Galactose Oxidase Obtained by Directed Evolution

Abstract: A directed evolution approach has been used for the generation of variants of galactose oxidase (GOase) that can selectively oxidize glycans on glycoproteins. The aldehyde function introduced on the glycans D-mannose (Man) and D-N-acetyl glucosamine (GlcNAc) by the enzyme variants could then be used to label the glycoproteins and also whole cells that display mannosides on their surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 31 publications
0
123
0
Order By: Relevance
“…From this collection, those that lacked residues predicted to act as copper ligands or else lacked the cysteine involved in the Tyr-Cys thioether bond were excluded from the set. Previous protein engineering and docking studies of FgGaOx identified Arg330, Phe464, Gln406, Phe194, Trp290, Tyr405, and Pro463 as potentially important for substrate binding (24,33,34). Therefore, sequences that differed at one or more of these positions, relative to the FgGaOx residues, were selected.…”
Section: Resultsmentioning
confidence: 99%
“…From this collection, those that lacked residues predicted to act as copper ligands or else lacked the cysteine involved in the Tyr-Cys thioether bond were excluded from the set. Previous protein engineering and docking studies of FgGaOx identified Arg330, Phe464, Gln406, Phe194, Trp290, Tyr405, and Pro463 as potentially important for substrate binding (24,33,34). Therefore, sequences that differed at one or more of these positions, relative to the FgGaOx residues, were selected.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to constructing a glucose 6-oxidase from GAO, enzyme engineering efforts have created GAO variant (M [3][4][5] ) that catalyse the enantioselective oxidization of secondary alcohols [98] and GAO variants (H 1 and F 2 ) that selectively oxidize glycans on glycoproteins [99]. While variant M [3][4][5] has been used to synthesize optically pure secondary alcohols and atropisomeric diaryl ethers [98,100], improved activity of H 1 and F 2 on D-mannose and D-N-acetyl glucosamine enabled selective labelling of glycoproteins in solution or present on the surface of whole cells [99].…”
Section: Altered Substrate Selectivitymentioning
confidence: 99%
“…While variant M [3][4][5] has been used to synthesize optically pure secondary alcohols and atropisomeric diaryl ethers [98,100], improved activity of H 1 and F 2 on D-mannose and D-N-acetyl glucosamine enabled selective labelling of glycoproteins in solution or present on the surface of whole cells [99]. Even though different mutagenesis techniques were applied to generate M 3-5 , H 1 and F 2 , all three acquired mutations of residue R330.…”
Section: Altered Substrate Selectivitymentioning
confidence: 99%
“…169 Toward expanding the substrate scope of galactose oxidase, directed evolution was used to select for enzyme variants that could oxidize mannose and GlcNAc residues. 172 Recently, Kohler and co-workers utilized both enzymatic and chemical oxidation to enrich and identify mammalian glycoprotein substrates for bacterial sialidases. 173 …”
Section: Enrichment Of Glycoproteins and Glycopeptidesmentioning
confidence: 99%